IMPLEMENTASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK SIKAP SOLIDARITAS SISWA - Shofa Nadya; Tatang Muhajang; Rini Sri Indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Implementation of Islamic Religious Education Values ​​in Forming Students'Solidarity Attitudes. Qualitative Research with a Descriptive Approach. Thesis ofthe Elementary School Teacher Education Study Program, Faculty of TeacherTraining and Education, Pakuan University, Bogor, 2025. This study describes theImplementation of Islamic Religious Education Values ​​in Forming Students'Solidarity Attitudes, the subjects of this study were 4 students who had not beenable to instill values ​​such as helping each other, tolerance, cooperation, andresponsibility in class V of Kalimulya 5 Elementary School, Depok City. Theresearch was conducted in the even semester of the 2024-2025 school year. RAP,MR, MA and DA as research subjects. The results of the study conducted throughobservation, interviews with subjects, homeroom teachers, religious teachers andparents showed that most students had not shown positive developments in theapplication of religious values ​​that form solidarity attitudes, there were stillchallenges in the form of individualism and low social awareness in somestudents. Factors that influence the implementation include the role of teachers,family environment, surrounding environment and religious school culture. Thisstudy emphasizes the importance of synergy between religious learning, teacherrole models, and parental involvement in fostering an attitude of solidarity from anearly age.